AOmpLib: an aspect library for large-scale multi-core parallel programming - Medeiros, Bruno Silvestre (2013)
This paper introduces an aspect-oriented library aimed to support efficient execution of Java applications on multi-core systems. The library is coded in AspectJ and provides a set of parallel programming abstractions that mimics the OpenMP standard. The library supports the migration of sequential Java codes to multi-core machines with minor changes to the base code, intrinsically supports the sequential semantics of OpenMP and provides improved integration with object-oriented mechanisms. The aspect- oriented nature of library enables the encapsulation of parallelism-related code into well-defined modules. The approach makes the parallelisation and the maintenance of large-scale Java applications more manageable. Furthermore, the library can be used with plain Java annotations and can be easily extended with application- specific mechanisms in order to tune application performance. The library has a competitive performance, in comparison with traditional parallel programming in Java, and enhances programmability, since it allows an independent development of parallelism-related code.